Pengaruh Iklim Organisasi dan Promosi Jabatan terhadap Kompensasi dan Dampaknya terhadap Komitmen Kerja Pegawai pada Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Muaro Jambi - Khairun Nisa; M. Zahari; Ali Akbar (J-MAS (Jurnal Manajemen dan Sains), 2023)
Every organization has a climate that makes employees feel that they are working in positive conditions in addition to providing promotions for outstanding employees. However, the material value of the compensation received tends to be a greater incentive to maintain or increase work commitment to the agency concerned. Where, this can be a positive or even negative trend for the agency if the management applied has not been able to penetrate all aspects directly related to the agency itself. Therefore, in this research will be carried out an analysis of the influence between each variable, either directly or indirectly. The research was conducted using descriptive analysis method to determine the scale and quantitative analysis (path analysis) based on the research variables used. The object of the research itself is the Regional Tax and Retribution Management Agency of Muaro Jambi Regency with a population and sample of 76 employees. The results of the study show that: 1) The total score of Organizational Climate (X1) and Compensation (Y) variables are in good category, while the Job Promotion variable (X2) and Work Commitment (Z) are in very good category; 2) Organizational Climate Variables (X1) and Position Promotion (X2) have a direct effect of 47.2% and an indirect effect of 52.8% on Compensation (Y); 3) Organizational Climate Variables (X1) and Job Promotion (X2) have a direct effect of 20.53% and an indirect effect of 79.47% on Work Commitment (Z); 4) Compensation Variable (Y) has a direct effect of 12% and another focus of 88% on Work Commitment (Z); and 5) Organizational Climate Variables (X1), Promotion (X2), and Compensation (Y) have a positive and significant effect on Work Commitment (Z).